Journal of the transactions of the Victoria Institute, or Philosophical Society of Great Britain. - Victoria Institute (Great Britain) (London : The Victoria Institute, 1866)
Each volume includes list of members, and "objects of the institute" (except v. 31, which has no list of members). Beginning with v. 12, a list of the papers contained in preceding volumes is issued regularly with each volume.
None published for 1898/99.
Vols. 1-5, also called 1st ser., v. 6- new series being the volumes containing the more modern papers.
Keywords: Religion and science -- Periodicals